School Bonding: Helping At-Risk Youth Become Students At-Promise (LEARNing Landscapes, 2007)
The purpose of this study was to determine if non at-risk and four types of at-risk secondary school students perceive school bonding differently. Findings indicate there are differences between the two groups of students on affective, cognitive and behavioral components of school bonding, although no differences were found between at-risk types. Girls showed stronger bonds to school while boys who were depressed were less affiliated to peers and fostered more negative attitudes towards teachers than other students.
Keywords: student engagement; at-risk students; affective; cognitive; behavioral; school bonding